(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-22-36 Abstract. Lexicographic portraiture can be successfully used as an efficient method of functional-semantic description of various groups of notional and functional vocabulary, the application of which is also advisable in the course of studying the system of modal verbs in the Scots language. The relevance and reliability of this method, as applied to Scots, is ensured by the availability and high quality of lexicographic reference books, which contain a comprehensive description of the lexis of this idiom. The verb will has been chosen as the object of description due to its significant role in the grammatical systems of both Scots and English. The aim of the study is to describe the functional and semantic features of the verb will in Older Scots in historical retrospective.The complex history of differentiation between such lexical-semantic variants of will as a notional verb, on the one hand, an auxiliary verb of an analytical aspectual-tense form and a substitute verb, on the other, and a modal verb (used as a semiauxiliary in a periphrastic construction), in between, necessitates turning to the historical and etymological constituent of the lexicographic portraiture of this lexeme at the first stage of the description. The article attempts to characterise, on the basis of lexicographic sources, the general picture of the historical development of the verb will in the written form of the Older Scots language. On the evidence of dialectological and historical-etymological dictionaries, a general picture of the existence of the verb will in the Older Scots language during the period from the 14th to the 17th century inclusive is obtained. The most abundant and complete historical information on the lexeme will is contained in the Dictionary of the Older Scottish Tongue, based on the monuments of written Older Scots. The differentiation between the use of will as a notional verb, on the one hand, and a modal, as well as a partially or fully grammaticalised verb of periphrastic constructions and analytical forms, on the other, according to this dictionary, occurs throughout the entire Older Scots period, with the gradual dying out of the first of the mentioned uses. All the lexical-semantic variants (LSVs) of the basic form will constitute a kind of functional-semantic continuum, the poles of which are constituted by the aforementioned notional option of the given verb, on the one hand, and the maximally grammaticalised option, on the other. Key words: modal verbs, lexicographic portraiture, the Scots language, the verb will, historical and etymological dictionaries Acknowledgements: the research was supported by the grant No. 24-28-00049 (https://rscf.ru/project/24-28-00049/) from the Russian Science Foundation.